2018
DOI: 10.1016/j.jsv.2018.03.027
|View full text |Cite
|
Sign up to set email alerts
|

On the effects of soil properties on leak noise propagation in plastic water distribution pipes

Abstract: In many countries, leaks are located in water distribution pipes by using the cross-correlation of pipe vibration measured either side of a suspected leak. However, in modern plastic pipes this can be problematic due to strong coupling between the water, the pipe and the soil, affecting the propagation of leak noise within the pipe. This paper concerns an analytical, numerical and experimental investigation into the way in which soil properties influence leak noise propagation in buried plastic water pipes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…The wave speed calculated is 497 m/s for data A and 377 m/s for data B. Compared with the theoretical wave speed of 540 m/s given in ref [8]…”
Section: Measurement Proceduresmentioning
confidence: 60%
“…The wave speed calculated is 497 m/s for data A and 377 m/s for data B. Compared with the theoretical wave speed of 540 m/s given in ref [8]…”
Section: Measurement Proceduresmentioning
confidence: 60%
“…In this section, based on the features of above-listed locating techniques, as well as the analysis and decision tree in [11,150], a flow chart for selecting the preferred pipe localization methods is illustrated in Figure 21. Furthermore, accurate evaluation in-situ acoustic properties of soils, especially wave speed, plays a significant role in the seismic wave method [101,102] and pipe leakage detection [143], as wave speed is directly related to the interpretation of measurement results. Therefore, many studies have been conducted on measurement of soil properties, which can be found in [144][145][146][147][148].…”
Section: Selection Of Pipeline Localization Methodsmentioning
confidence: 99%
“…The effects of the soil properties on wave propagation in a buried pipe, such as that shown in Fig. 2, have been investigated by Muggleton et al [18], Muggleton and Yan [23], Gao et al [24,25] and Brennan et al [26]. Here, the most complete model of the buried water pipe system, which is described in [24], is used in the determination of the soil properties.…”
Section: Effects Of Soil Properties On the Propagation Of Leak Noisementioning
confidence: 99%
“…It is known that the soil properties have a profound effect on both the speed of the leak noise propagation along the pipe (wave speed), and the attenuation of this wave [22][23][24][25][26]. The works discussed hitherto did not model the soil effectively, as it was treated as a fluid supporting elastic waves in the soil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation